2008
DOI: 10.1016/j.ejcts.2007.12.015
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for occult nodal metastasis in clinical T1N0 lung cancer: a negative impact on survival

Abstract: Clinical T1N0 tumors are often understaged. The risk of occult nodal disease increases with tumor size, and this occult disease negatively impacts survival. Because of the limitations of clinical staging, we believe that lobectomy and lymph node analysis should be offered to cT1N0 lung cancer patients to provide accurate staging and to optimize multimodality adjuvant treatment of lung cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
40
0
2

Year Published

2010
2010
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(48 citation statements)
references
References 22 publications
6
40
0
2
Order By: Relevance
“…Staging of Lung Cancer histology) and tumor size and location (larger size, central location), are associated with a higher risk of occult nodal disease and should be considered in the decision as to whether to perform invasive nodal sampling. 37,38 FDG PET and FDG PET/CT have improved sensitivity and specificity for detecting mediastinal nodal metastasis compared with CT (Fig. 5).…”
Section: Regional Lymph Nodesmentioning
confidence: 94%
“…Staging of Lung Cancer histology) and tumor size and location (larger size, central location), are associated with a higher risk of occult nodal disease and should be considered in the decision as to whether to perform invasive nodal sampling. 37,38 FDG PET and FDG PET/CT have improved sensitivity and specificity for detecting mediastinal nodal metastasis compared with CT (Fig. 5).…”
Section: Regional Lymph Nodesmentioning
confidence: 94%
“…Although the intraoperative conduct of surgeons cannot be measured in this retrospective series, it is our observation that tumor size may have influenced surgeon behavior as larger tumors were statistically associated with more aggressive LNS and RNs. Veeramachaneni and colleagues [26] looked at tumor size in clinical T1N0 patients (where 68% underwent staging mediastinoscopy) and found that tumor size directly related to cancer lethality and was a significant predictor of lymph node metastasis. Interestingly, there was only a 0.2 cm difference in median tumor size in patients found to have occult lymph node metastases compared with those that were lymph node negative.…”
Section: Commentmentioning
confidence: 98%
“…Hilar and mediastinal lymph nodes were classified as with positive cancer involvement if the short-axis diameter exceeded 10 mm on contrast-enhanced CT images or evidences of uptakes showed on PET scans. Based on previous reports [1,4,5], patients with lymph node diseases diagnosed by PET or CT criteria were not excluded in this study.…”
Section: Staging System and The Definition Of Nodal/distant Metastasesmentioning
confidence: 99%
“…Tumor size in non-small cell lung cancer (NSCLC) is associated with nodal [1][2][3] and distant metastases [4,5], and is an independent prognostic factor for survival [6][7][8]. Different tumor size cutoff points are advocated in studies regarding the association between tumor size, metastatic rate and survival differences.…”
Section: Introductionmentioning
confidence: 99%